2022
DOI: 10.1111/fwb.13910
|View full text |Cite
|
Sign up to set email alerts
|

Alpha and beta diversity and species co‐occurrence patterns in headwaters supporting rare intermittent‐stream specialists

Abstract: Intermittent rivers are the focus of a burgeoning subdiscipline of freshwater science, driven by mounting recognition of their ubiquity, biodiversity, and climate sensitivity. However, our understanding of their ecology is hampered by a reliance on unstandardised diversity measures, an underrepresentation of certain stream types in metacommunity research and a reticence to acknowledge biotic interactions as a potentially fundamental driver of catchment‐scale patterns in assemblage composition. This study analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 100 publications
1
9
1
Order By: Relevance
“…Between‐habitat variation in turnover is known to arise from differences in connectivity and/or greater seasonal disturbance (Tonkin et al 2017, Perkin et al 2021, Aspin and House 2022). However, higher turnover might also be expected in the river‐floodplain systems simply due to their higher species richness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Between‐habitat variation in turnover is known to arise from differences in connectivity and/or greater seasonal disturbance (Tonkin et al 2017, Perkin et al 2021, Aspin and House 2022). However, higher turnover might also be expected in the river‐floodplain systems simply due to their higher species richness.…”
Section: Discussionmentioning
confidence: 99%
“…For example, some studies of intermittent streams have found that nestedness contributes more to temporal β-diversity in high-order headwaters subject to extreme stochastic drying, whereas turnover plays a more significant role in lower-order streams with more predictable seasonality (Datry et al 2016, Perkin et al 2021. However, other studies have reported contradictory findings (Aspin and House 2022).…”
Section: Discussionmentioning
confidence: 99%
“…We quantified alpha diversity using two metrics, taxa richness (the number of taxa per sample, as a widely used and thus easily interpretable metric) and coverage‐adjusted HS diversity. HS diversity was calculated using the ‘iNext’ package (version 3.0.0, Hsieh et al, 2016), in which rarefaction and extrapolation were used to standardize all samples to 95% coverage, accounting for differences in taxon detection between samples (Aspin & House, 2022; Roswell et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…We attribute this lack of response to the considerable compositional variability both within and among communities at sites with perennial and temporary flow. In turn, this variability was likely driven by the infrequent occurrence of many taxa (Aspin & House, 2022); the geographical isolation of headwaters, which promotes the establishment and maintenance of distinct communities (Finn et al, 2011;Sarremejane et al, 2017); and the recorded habitat heterogeneity.…”
Section: Metric Relationships With Environmental Variablesmentioning
confidence: 99%
See 1 more Smart Citation